Conscripts of Migration : Neoliberal Globalization, Nationalism, and the Literature of New African Diasporas - Foster, Christopher Ian (Book collections on Project MUSE., 2019)
"In Conscripts of Migration: Neoliberal Globalization, Nationalism, and the Literature of New African Diasporas, author Christopher Ian Foster analyzes increasingly urgent questions regarding crises of global immigration by redefining migration in terms of conscription and by studying contemporary literature. Reporting on immigration, whether liberal or conservative, popular or scholarly, leaves out the history in which the global North helped create outward migration in the global South. From histories of racial capitalism, the trans-Atlantic slave trade, and imperialism to contemporary neoliberal globalization and the resurgence of xenophobic nationalism, countries in the global North continue to devastate and destabilize the global South. Britain, France, Italy, and the United States, in different ways, police the effects of their own global policies at their borders."--Provided by publisher.